Proceedings of the Seventh Annual ACM/IEEE International Conference on Human-Robot Interaction 2012
DOI: 10.1145/2157689.2157699
|View full text |Cite
|
Sign up to set email alerts
|

Consistency in physical and on-screen action improves perceptions of telepresence robots

Abstract: Does augmented movement capability improve people's experiences with telepresent meeting participants? We performed two web-based studies featuring videos of a telepresence robot. In the first study (N=164), participants observed clips of typical conversational gestures performed a) on a stationary screen only, b) with an actuated screen moving in physical space, or c) both on-screen and in-space. In the second study (N=103), participants viewed scenario videos depicting two people interacting with a remote co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Second, compared with distributed teams or remote partners, colocated teams have less trouble developing trust, coordinating work, resolving conflict, and engendering high motivation (Hinds and Bailey, 2003). Third, it was also reported that social telepresence was enhanced when the remote person's movement was augmented by a display's physical movement (Adalgeirsson and Breazeal, 2010;Nakanishi et al, 2011;Sirkin, 2012). Finally, in robot-mediated communication, the depth from motion parallax could increase the visibility of body motions.…”
Section: Robotmentioning
confidence: 99%
“…Second, compared with distributed teams or remote partners, colocated teams have less trouble developing trust, coordinating work, resolving conflict, and engendering high motivation (Hinds and Bailey, 2003). Third, it was also reported that social telepresence was enhanced when the remote person's movement was augmented by a display's physical movement (Adalgeirsson and Breazeal, 2010;Nakanishi et al, 2011;Sirkin, 2012). Finally, in robot-mediated communication, the depth from motion parallax could increase the visibility of body motions.…”
Section: Robotmentioning
confidence: 99%
“…Establishing the external validity of the questionnaire, items were achieved by means of literature review of relevant articles [12,[15][16][17] and collaborative work with a group of early childhood education experts, preschool teachers, Is a Robot better than Video for Initiating Remote Social Connections among Children? educational technology engineers, and robotics engineers.…”
Section: Methodsmentioning
confidence: 99%
“…To this, Kapur adds that "[w]aiting backstage to go on, and important aspects of socialisation after a performance, are not the same over a network", leading to a "loss of society within the band" [26]. In that sense, distributed performance shares a common challenge with ComputerSupported Cooperative Work, a set of activities that also often exhibit a decreased sense of mutual awareness and spontaneous interaction [16] [38]. In fact, we regard distributed performance as a unique application area of the "same time/different place" category of CSCW [25].…”
Section: Related Workmentioning
confidence: 99%
“…. we (perhaps subconsciously) prefer that our technological counterparts follow suit" [38]. An example of a system designed to support such cues, and which directly inspired our display topology, is Hydra, a set of independent communication units, each with its own video display, microphone and speaker.…”
Section: Related Workmentioning
confidence: 99%